"Give me some space": exploring youth to parent aggression and violence - Gabriel, Lynne (Journal of family violence, 2018)
A small scale qualitative project, undertaken by an interdisciplinary domestic violence research group involving academic researchers and research assistants, with colleagues from Independent Domestic Abuse Services (IDAS), investigated youth aggression and violence against parents. Following the literature review, data was generated through several research conversations with young people (n = 2), through semi-structured interviews with mothers (n = 3) and practitioners (n = 5), and through a practitioner focus group (n = 8). Thematic analysis and triangulation of the data from parents, practitioners and young people, elicited interconnected and complex overarching themes. Young people could be both victim and perpetrator. The witnessing or experiencing of domestic aggression and violence raised the concept of ‘bystander children’. The impact of young people experiencing familial violence was underestimated by parents. For practitioners, the effects of working with domestic violence was shown to be significant - both positively and negatively.